SYMBOLIC FUNCTIONS OF FOOD IN SELECTED INDONESIAN CHILDREN’S WRITINGS KKPK SERIES - Retno Wulandari; Dinie Ratri Desiningrum (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
Abstract Food is one of the elements that can reveal the society’s dynamic, beliefs, ideology, and values. The relation of food and literature is inevitable as food is part of culture, then the relations of characters in a work of literature may involve food. This paper is intended to investigate the symbolic functions of food in some Indonesian children’s writings Kecil-Kecil Punya Karya (KKPK) series, namely Izzati’s Let’s Bake Cookies, Alifia’s Egg Ice Cream, and Haura’s Resep Baru (New Recipe). The umbrella of the theory is Roland Barthes’ food as signifying system and it is applied in the context of children’s literature. In addition, to scrutinize the cultural-social and production of the work, Bourdieu’s field of cultural production theory is applied. Close-reading is used to collect data in the three writings. The data are tabulated and then analyzed through sociological approach and using descriptive analysis method. The result shows that in that literary works food functions as: 1) arena for socialization and solidarity; 2) identity marker, both for social and self identity; 3) social class marker; and 4) arena for negotiation for global and local culture. Keywords: food, symbolic function, children’s writing METAFORA MAKANAN DALAM SASTRA ANAK INDONESIA SERI KKPK AbstrakMakanan merupakan salah satu elemen penting yang mampu mengungkapkan dinamika masyarakat, kepercayaan, ideologi, dan nilai-nilai. Hubungan antara makanan dan sastra tidak terelakkan lagi karena makanan merupakan bagian dari budaya, sehingga hubungan karakter dalam suatu karya sastra seringkali melibatkan makanan.Tulisan ini bertujuan menelaah fungsi simbolik makanan dalam tulisan anak Indonesia seri Kecil-Kecil Punya Karya (KKPK) : Let’s Bake Cookies karya Izzati, Egg Ice Cream karya Alifia, dan Resep Baru karya Haura. Payung teori yang digunakan adalah teori dari Roland Barthes yang menyatakan makanan sebagai sistem tanda yang diaplikasikan dalam konteks sastra anak Indonesia. Selain itu, teori Bourdieu mengenai ranah produksi kultural juga diterapkan untuk menganalisis situasi sosial, budaya, dan produksi di luar karya sastra. Membaca teliti (close- reading) digunakan untuk mengumpulkan data. Data tersebut ditabulasi dan kemudian dianalisis melalui pendekatan sosiologis dan menggunakan metode deskriptif analisis. Hasil menunjukkan bahwa dalam karya-karya sastra anak tersebut makanan berfungsi sebagai: 1) ajang untuk sosialisasi dan solidaritas; 2) penanda identitas, baik identitas sosial dan identitas diri; 3) penanda kelas sosial; dan 4) sebagai ajang negosiasi budaya global dan lokal. Kata kunci: makanan, fungsi simbolik, sastra anak